Performance Analysis of Chirped Graded Photonic Crystal Resonator for Biosensing Applications - Jasmine Saini; Ajay Kumar; Amit Kumar Goyal (Photonics)
In this manuscript, a chirped graded photonic crystal (PhC) resonator structure is optimized for biosensing applications. The proposed structure comprises a bilayer PhC with an aqueous defect layer, where the thickness grading within the material is introduced, considering alpha (<semantics>α</semantics>) as a grading parameter. The device performance is analytically evaluated using the finite element method (FEM). The impact of <semantics>α</semantics>, the resonator thickness, and the incidence angle on the device performance is analyzed. Further, the device’s ability to be used as a biosensor is evaluated, considering cholesterol as an analyte. The analytical results demonstrate an average sensitivity of 410 nm/RIU, a quality factor of 0.91 × <semantics>103</semantics>, and a figure of merit (FOM) of 2.47 × <semantics>102</semantics><semantics>RIU−1</semantics>, showing 88.5% and 43% improvements in sensitivity and FOM compared to recently reported devices. The device’s superior sensing performance makes it suitable for medical and commercial applications, while the use of thickness grading addresses fabrication limitations, offering a robust framework for advanced photonic device design.